The role of surfactant proteins SP-A and SP-D in viral infection: a focus on COVID-19 - O. S. Kharlamovа; K. Yu. Nikolaev; Yu. I. Ragino (Бюллетень сибирской медицины, 2022)
An immune response to invasion of viral pathogens is an integral part of maintaining the physiological functioning of the bronchopulmonary system and effective gas exchange. Collagen-containing C-type lectins (lung collectins) are some of the key proteins in the identification of viral particles. They have image-recognizing receptors that identify pathogen-associated molecular patterns, particularly viral glycoproteins. The surfactant proteins SP-A and SP-D, which are composed of trimerized units, belong to pulmonary collectins and oligomerize into higher-order structures. These proteins play an essential role in recognition and elimination of microbial pathogens (viruses, bacteria, fungi, parasites, nanoparticles, allergens) through a variety of mechanisms. Taking into account the burden of the novel coronavirus infection caused by the SARS-CoV-2 virus, it is important to consider the role of the surfactant proteins SP-A and SP-D in the pathogenesis of the immune response to viral invasion. Currently, there are data on the direct relationship between surfactant proteins and viruses belonging to the Coronaviridae family. The SP-A and SP-D proteins modulate inflammatory responses and cytokine synthesis, but prevent an excessive inflammatory response (cytokine storm). There is also an assumption that SARSCoV-2 directly suppresses and alters the production of surfactant proteins. Thus, the key pathogenetic role of the surfactant proteins SP-A and SP-D in the response to the viral pathogen SARS-CoV-2 is evident. Today, this is a promising area of translational medicine, which will contribute to a profound understanding of the pathogenesis of coronavirus infection for assessing the diagnostic and prognostic potentials of the surfactant proteins SP-A and SP-D in COVID-19. Additionally, it will help evaluate the therapeutic potential of recombinant fragments of human SP-A and SP-D.